Application of Augmented Reality to Replicate Couples Sit in Wedding Ceremony - Achmad Ariq Rivaldhi; Rohman Dijaya (JOIN (Jurnal Online Informatika), 2021)
In Indonesia, the bride and groom do pre-wedding photos like a tradition before marriage with couple sit in wedding ceremony. The splendor of the wedding ceremony made many vendors interested in running a wedding party business. These vendors provide services and goods related to wedding parties, such as wedding organizers, bridal, party decorations (couples sit in of wedding ceremony), as well as photo and video documentation. To give more virtual wedding nuance experience to customer, augmented reality was applied. This research develop application of augmented applying to replicate couples sit in of wedding ceremony. Augmented reality (AR) technology adopted to promote couples sit in of wedding ceremony. Moreover, combines wedding ceremony nuance and augmented reality make consumers who want to find 3D wedding background desired.